Evaluation Approach Interdisciplinary in Mitigation Education Disasters in Elementary Schools: Literature Review and Implications - Renni Ramadhani Lubis; Dwiningrum, Siti Irene Astuti; Supartinah (Journal of Elementary School Education, 2024)
This study aim for evaluate approach i nterdisciplinary in mitigation disaster at school base with analyze in a way detailed from various source literature. This study use method study literature.Technique data collection used that is articles that have been published in journals national and international in 2020-2024, which examines variety approach interdisciplinarity used, challenges faced in its application and impact to results study student. Based on results research, it is known that results analysis give description comprehensive How integration eye lesson can influence effectiveness initiative mitigation disaster level education base. With integrate various discipline knowledge like knowledge nature, science social and civic to in curriculum, we can create more approach holistic and coordinated to situation disaster. Through method learning interdisciplinary and strengthening skills practical, initiative mitigation disaster can become more effective and meaningful for student school basic, helpful they no only understand risk, but also encouraging development of more prevention strategies good. Implications from study this is very important for development policies and practices education related mitigation disaster at school base. Therefore that, this research not only give outlook about successes and challenges approach interdisciplinary, but also inspiring action constructive for increase resilience generation young to future disaster.